Comparative study of the anti-tumour effects of the imipridone, ONC201 and its fluorinated analogues on pancreatic cancer cell line - Zsófia Szász; Angéla Takács; Márton Kalabay; Péter Bárány; Tamás Czuczi; Antal Csámpai; Eszter Lajkó; László Kőhidai (Scientific Reports)
Abstract Pancreatic ductal adenocarcinoma has a high mortality rate, with a 5-year survival rate of ~ 12%. Therefore, developing new targeted therapies is urgently needed. ONC-201, a promising candidate, is currently undergoing clinical trials. The main objective of the present work is to investigate the anti-tumour activity of ONC-201 and its two fluorinated analogues (TBP-134, TBP-135). The viability of two pancreatic adenocarcinoma cell lines (PANC-1, MIA PaCa-2) and three other tumour cell lines (A2058, EBC-1, COLO-205) was assessed after 72-hour treatment with drugs at 0.5, 10, and 25 µM. Significant antiproliferative effects were observed, with 0.5 µM TBP-134 achieving the highest potency, reducing cell viability to approximately 50%. None of the molecules exhibited significant cytotoxicity toward normal human dermal fibroblast cells or cardiomyocytes, indicating a selective anti-tumour profile. The analogues showed more effective results than ONC201 on PANC-1 cells (IC50: 0.35 and 1.8 µM vs. IC50: 6.1 µM, respectively). All analogues induced G2/M phase arrest followed by apoptosis in PANC-1 cells. The site of the fluorination influenced the mechanism of apoptotic action of these compounds. Overall, TBP-134 showed superior efficacy, making it a promising candidate for structural optimization within the imipridone family to develop more effective, selective treatments for pancreatic tumours.